PEMBERDAYAAN KELOMPOK EKONOMI PRODUKTIF MELALUI PELATIHAN PEMBUATAN PUPUK ORGANIK DARI KULIT PISANG - Hartati, Tri Mulya; Dwiputranti, Oktora (Jurnal Pengabdian Kepada Masyarakat Undana, 2021)
ABSTRACT The existence of the Covic-19 pandemic also affects the economic factors of the community that interfere with the immune system, so there is a need for productive activities that can increase added value. Banana peel utilization technology aims to train the community in dealing with plant waste management. This community service activity was carried out in Ngade Village, South Ternate District, Ternate City Regency. The target of the service participants is a group of young people who are members of the productive economic group "Qonita". The method used is the indirect method and the learning by doing method by demonstrating and conducting counseling about the manufacture of organic fertilizer made from banana peels. The activities provided include counseling and training on making organic fertilizer from banana peels. All activities are carried out online and offline while still implementing the Covic-19 protocol. To find out the increase in understanding of the partner group, an evaluation was designed at the beginning (pre test) and at the end of the activity (post test). From the pre-test and post-test scores, the results of the implementation of this activity showed that the insight ability of the "Qonita" youth group increased by 81.6%. The socialization of making organic fertilizer made from banana peels provides additional insight for the youth group "Qonita" in utilizing agricultural waste. ABSTRAK Adanya pandemi Covic-19 turut mempengaruhi faktor ekonomi masyarakat yang mengganggu sistem imun sehingga perlu adanya kegiatan produktif yang dapat meningkatkan nilai tambah. Teknologi pemanfaatan kulit pisang bertujuan untuk melatih masyarakat dalam mengatasi penanganan limbah tanaman. Kegiatan pengabdian pada masyarakat ini dilaksanakan di Kelurahan Ngade Kecamatan Ternate Selatan, Kabupaten Kota Ternate. Sasaran peserta pengabdian adalah kelompok pemuda pemudi yang tergabung dalam kelompok ekonomi produktif “Qonita”. Metode yang digunakan metode tak langsung dan metode learning by doing dengan mendemontrasikan dan mengadakan penyuluhan tentang pembuatan pupuk organik berbahan kulit pisang. Kegiatan yang diberikan meliputi penyuluhan dan pelatihan pembuatan pupuk organik dari kulit pisang. Semua kegiatan dilakukan secara daring dan luring dengan tetap menerapkan protokol Covic-19. Untuk mengetahui peningkatan pemahaman kelompok mitra, dirancang suatu evaluasi yang dilakukan di awal (pre test) dan akhir kegiatan (post test). Dari nilai pre test dan post test, hasil pelaksanaan kegiatan ini menunjukkan bahwa kemampuan wawasan kelompok pemuda pemudi “Qonita” meningkat sebesar 81,6%. Sosialisasi pembuatan pupuk organik berbahan kulit pisang memberikan tambahan wawasan bagi kelompok pemuda pemudi “Qonita” dalam memanfaatkan limbah pertanian